1996
DOI: 10.1073/pnas.93.3.1221
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity analysis of thanatin, a 21-residue inducible insect defense peptide with sequence homology to frog skin antimicrobial peptides.

Abstract: Immune challenge to the insect Podisus maculiventris induces synthesis of a 21-residue peptide with sequence homology to frog skin antimicrobial peptides of the brevinin family. The insect and frog peptides have in common a C-terminally located disulfide bridge delineating a cationic loop. The peptide is bactericidal and fungicidal, exhibiting the largest antimicrobial spectrum observed so far for an insect defense peptide. An all-D-enantiomer is nearly inactive against Gram-negative bacteria and some Gram-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
266
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(281 citation statements)
references
References 20 publications
14
266
0
1
Order By: Relevance
“…It has not previously been reported that thanatin has antifungal activity against the rice blast pathogen M. oryzae, although this was expected because thanatin has wide-ranging activity against many kinds of fungi (Fehlbaum et al 1996). As shown in Fig.…”
Section: Acquired Resistance Of the Transformant To Rice Blastmentioning
confidence: 95%
See 3 more Smart Citations
“…It has not previously been reported that thanatin has antifungal activity against the rice blast pathogen M. oryzae, although this was expected because thanatin has wide-ranging activity against many kinds of fungi (Fehlbaum et al 1996). As shown in Fig.…”
Section: Acquired Resistance Of the Transformant To Rice Blastmentioning
confidence: 95%
“…Antimicrobial activity was determined as previously described, using Micrococcus luteus in 96-well microtiter plate, to which were added 10 g of crude plant extract or 10 l of the high-performance liquid chromatography ( Luteus (Fehlbaum et al 1996).…”
Section: Bioassay Of Antimicrobial Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…(c) Thanatin Thanatin is a 21-residue cationic peptide with sequence homology to frog skin antimicrobial peptides of the brevinin family (31,32). It has a single disulfide bridge and exhibits a remarkably large spectrum of activity against both Grampositive and Gram-negative bacteria and against filamentous fungi.…”
Section: (B) Drosomycinmentioning
confidence: 99%